Characterization of the Polyphenolic Profiles of Peel, Flesh and Leaves of Malus domestica Cultivars Using UHPLC-DAD-HESI-MSn - Petkovska, Ana; Gjamovski, Viktor; Stanoeva, Jasmina Petreska; Stefova, Marina (SAGE Publications, 2017)
Qualitative and quantitative analyses of polyphenols extracted from 21 Malus domestica cultivars using ultra high performance liquid chromatography with diode array detection coupled to heated electrospray ionization mass spectrometric detection was performed for separation of 27 phenolic compounds on a reversed phase UHPLC column with an optimized gradient consisting of 1% formic acid in water and 1% formic acid in methanol within 20 minutes. According to retention times, UV maxima and mass spectra of the peaks in the chromatograms obtained from extracts of apple peel, flesh and leaves, the polyphenolic compounds were identified and quantified. Based on fragmentation patterns, 6 phenolic acids, 5 flavan-3-ols, 5 dihydrochalcones, 8 flavonols and 3 flavone derivatives were characterized in the studied samples. The method was then employed for analysis of the polyphenolic pattern of 21 apple cultivars, both commercial and autochthonous for the Macedonian region, as well as for monitoring the influence of long term storage on the polyphenolic content and composition of apple fruits and for comparison of polyphenolic profiles of apple cultivars during two years of harvesting. The obtained results revealed minor differences in the quality and major variation in the content of phenolic compounds in the flesh, peel and leaves in the studied apple cultivars that is attributed mainly to cultivar differences and meteorological factors.